EFEKTIVITAS ANTIHIPERGLIKEMIK PADA KELINCI JANTAN DARI EKSTRA ETANOL BUNGA TELANG (Clitoria Ternatea) - riana Versita; Nori Wirahmi; Nova Yustisia; Oky Hermansyah (Sekolah Tinggi Kesehatan Al-Fatah Bengkulu, 2022)
Telang flower plant (Clitoria ternatea) is a leguminous plant belonging to the Fabaceae family, containing bioactive compounds that are useful for treatment. Its ability as a biologically active compound gives a great role to human interests. Phenolic compounds have a positive correlation with antioxidant activity, so that polyphenols are probably the compounds that have the most potential to contribute anti-radical activity in telang flower. Telang flower extract has many properties so it is used as a traditional medicine for several diseases. A number of studies have shown that flavonoids have antiviral, anti-allergic, antiplatelet, antidiabetic, diuretic, anti-inflammatory, antitumor, and antioxidant activities. The phytochemical content of telang flower which is efficacious as antidiabetic / antihyperglycemic is saponins and flavonoids. Based on this, a preliminary study was conducted to determine the effectiveness of ethanol extract of telang flower (Clitoria ternatea) against antihyperglycemic in male rabbits. This type of research is a laboratory experiment. Telang flower powder simplicia (Clitoria ternatea) was extracted using the maceration method. Telang flower (Clitoria ternatea) ethanol extract was made in 3 concentrations, namely 2%, 3% and 4%. Antohyperglycemic effectiveness test used 3 groups, namely negative control (without treatment), positive control (Glibenclamide), ethanol extract of telang flower (Clitoria ternatea) 2%, 3% and 4%, against 4 white rabbits weighing 3-3.5 kg and given sucrose, carried out until the 8th day. The data were statistically processed using One Way ANOVA (Analysis Of Variant). In conclusion, giving ethanol extract of telang flower (Clitoria ternatea) with concentrations of 2%, 3%, and 4% at 60 minutes gave an effective and significant reduction in blood glucose levels compared to negative control and positive control.